Economic dispatch with environmental consideration using Particle Swarm Optimization (PSO) / Muhd Azri Abdul Razak - Abdul Razak, Muhd Azri (2012)
Efficient load allocation to several generating unit in a power plant can reduce harmful gases emission that give bad impact to human and environment. The best method to allocate the power of generating units is by applying economic dispatch (ED). The primary objective of economic dispatch (ED) is to minimize the total generation cost while satisfying the constraint or the condition that are essential to operation. In this study, emission is proposed to be minimized together with generation cost known as Emission and Economic Dispatch (EED) instead of Economic Dispatch (ED) alone. Particle Swarm Optimization (PSO) algorithm was implemented in emission economic dispatch (EED) calculation in order to obtain optimum power generation of each generating unit to satisfy consumer demand and loses. This method is applied to IEEE 30-bus with six generation unit assumed to be run at all time. The best power allocation for each generating unit that is generated at the end of the optimization process also will minimized total generation cost and emission of sulphur oxide (SOx), nitrogen oxide (NOx) and carbon dioxide (CO2) gases after evaluation of the fitness function.